2021
DOI: 10.1002/hep.31725
|View full text |Cite
|
Sign up to set email alerts
|

Human Hepatitis B Virus Negatively Impacts the Protective Immune Crosstalk Between Natural Killer and Dendritic Cells

Abstract: BaCKgRoUND aND aIMS: Natural killer (NK) cells play a crucial role in the clearance of human viruses but their activity is significantly impaired in patients infected with chronic hepatitis B (CHB). Cooperation with dendritic cells (DCs) is pivotal for obtaining optimal NK cell antiviral function; thus, we investigated whether HBV might impact the ability of DCs to sustain NK cell functions. appRoaCH aND ReSUltS: Human DCs were poor stimulators of interferon-gamma (IFNγ) production by NK cells when exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Although pDCs exist as a small proportion of the total cells in blood, they are the main effector cells producing type I interferon in vivo and play a vital role in HBV infection. However, functional defects in pDCs have been reported in patients with chronic HBV infection ( 18 , 19 , 27 ). At present, the ultimate goal of CHB treatment is to achieve functional cure, which requires antiviral immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Although pDCs exist as a small proportion of the total cells in blood, they are the main effector cells producing type I interferon in vivo and play a vital role in HBV infection. However, functional defects in pDCs have been reported in patients with chronic HBV infection ( 18 , 19 , 27 ). At present, the ultimate goal of CHB treatment is to achieve functional cure, which requires antiviral immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive activation of immune suppressor cells can lead to persistent HBV infection and progression of HCC. The immunosuppressive effect of cells involved in negative immune regulation causes CD8+ T and NK cells to become exhausted, allowing HBV and HCC tumor cells to escape the immune system [ 22 , 72 , 93 , 94 ]. The key immunosuppressive T cell subset, Treg cells, mainly produces immunosuppressive cytokines including TGF-β, IL-10, and IL-35 [ 72 ].…”
Section: Regulation Among Different Immune Cells In Hbv-related Hccmentioning
confidence: 99%
“…A recent study found that plasmacytoid DC function was greatly reduced in patients with CHB, and IL6ST (gp130) played a key role in contributing to DC dysfunction [ 92 ]. Another study showed that HBV causes abnormal NK–DC interplay that may impair the efficacy of antiviral immune responses in patients with CHB [ 93 ].…”
Section: Regulation Among Different Immune Cells In Hbv-related Hccmentioning
confidence: 99%
“…With great interest, we read the manuscript by De Pasquale et al ( 1 ) They convincingly showed that dendritic cells (DCs), generated in vitro from monocytes of patients with HBV, have a detrimental effect on the function of natural killer (NK) cells, leading to the insufficient anti‐HBV response observed in patients with chronic HBV. However, many years ago, we conducted a similar study.…”
mentioning
confidence: 99%